Analisis Pengaruh Perpindahan Merek melalui Harga, Iklan dan Ketidakpuasan Konsumen - Sulistyo, Budhi Ade; Maftukhah, ida (Management Analysis Journal, 2016)
The aim of this study was to investigate the influence of positive pricing, advertising, and consumer dissatisfaction against brand switching of courirer services company partially or simultaneously.The research sample was determined using iterations formula method with a total of 118 respondents using Purposive Sampling.Methods of data collection using questionnaires that measured using a Likert scale. The analyze percentage is using descriptive analysis and multiple regression analysis.The conclusions is the higher of price offered, the more likely consumers switch brands to PT JNE, increasingly active ads, the more likely consumers switch brands to PT JNE, and the higher level of consumers dissatisfaction, the more likely consumers switch to PT JNE.